PEMBUATAN PRODUK INOVASI KERIPIK SAWO DI DESA MLANDINGAN WETAN KABUPATEN SITUBONDO - Wahyuningsi, Nurin Kartika; Husna, Zahra Nafilatul; Idris, Albani; Romla, Siti; Jannah, Raudatul (Jurnal Pemberdayaan Masyarakat dan Inovasi, 2025)
Mlandingan Wetan Village has various interesting potentials starting from the abundant harvest in the village and innovations have not been carried out such as the presence of sapodilla fruit falling in residents' yards. The gap between the large potential of sapodilla fruit and the limited products is an important reason for implementing community service in Mlandingan Wetan Village. In order to utilize the knowledge gained regarding village product innovation that can increase the value of a product by utilizing the potential of natural resources in a village to be able to improve the economy of residents in Mlandingan Wetan by innovating the processing of sapodilla fruit into sapodilla fruit chips. PBPMD participants finally carried out the innovation of "Sapodilla Chips Production" after several work programs that became alternatives when observing village potential. The results of the PBPMD participant innovation brought several positive results for the community, both in terms of economy and social. During the sapodilla chip production process, the community was very enthusiastic and also enthusiastic, so that with enthusiasm the community's spirit went according to plan. Of course, these good results were achieved thanks to the support and cooperation of PBPMD STKIP PGRI Situbondo students.